Sustainable public procurement through Internet of Things and cloud computing in South Africa - Lawrence M. Mojaki; Tite Tuyikeze; Nkanyiso K. Ndlovu (Africa’s Public Service Delivery & Performance Review)
Background: The South African public sector uses procurement and supply chains to address service delivery mandates. This approach must be based on a system that is inclined to ‘value for money, open and effective competition, ethics and fair dealing, accountability and reporting, and equity’. The current system is plagued by biasedness, poor record handling and insufficient contract administration.